A Systematic Review of In Vivo Studies of the Efficacy of Herbal Medicines for Anti-Aging in the Last Five Years - Seung-Yeon Cho; Han-Gyul Lee; Seungwon Kwon; Seong-Uk Park; Woo-Sang Jung; Sang-Kwan Moon; Jung-Mi Park; Chang-Nam Ko (MDPI AG, 2023)
Background: The world's population is rapidly aging, and attention to and research on the increase in life expectancy and age-related diseases are needed. This study aimed to review the in vivo studies on the anti-aging effects of herbal medicines. Methods: In vivo studies of single or complex herbal medicines for anti-aging that were published in the last five years were included in this review. The following databases were used: PubMed, Scopus, ScienceDirect, Web of Science and EMBASE. Results: A total of 41 studies were considered eligible for the review. The articles were classified into body organs and functions, experimental country, herbal medicine, extraction method, administration route, dosage, duration, animal model, aging-induced method, sex, number of animals per group, and outcomes and mechanisms A single herbal extract was used in a total of 21 studies including Alpinia oxyphylla Miq., Acanthopanax senticosus and Lyceum barbarum, and a multi-compound herbal prescription was used in a total of 20 studies, including Modified Qiongyu paste, Wuzi Yanzong recipe, etc. Each herbal medicine had anti-aging effects on learning and memory, cognition, emotion, internal organs, gastrointestinal tracts, sexual functions, musculoskeletal function and so on. The common mechanisms of action were antioxidant and anti-inflammatory, and various effects and mechanisms for each organ and function were identified. Conclusions: Herbal medicine exhibited beneficial effects on anti-aging in various parts of the body and its function. Further investigation of the appropriate herbal medicine prescriptions and their components is recommended.